Early Post-Discharge Suicide in Mental Health Patients: Findings From a National Clinical Survey - Bojanić, Lana; Hunt, Isabelle M.; Baird, Alison; Kapur, Navneet; Appleby, Louis; Turnbull, Pauline (Frontiers in Psychiatry, 2020)
Studies on suicide by recently discharged mental health patients have reported a high number of deaths in the early post-discharge period, which has led to recommendations of follow-up within seven days. More recently, the National Confidential Inquiry into Suicide and Safety in Mental Health (NCISH) proposed a more ‘stringent’ follow-up period of two to three days after discharge. Patients who died within this early time-frame post-discharge were more likely to die before the follow-up appointment occurred. They more often had a primary diagnosis of a personality disorder, self-discharged and had a higher frequency of death by jumping from a height or in front of the vehicle compared to later deaths. This study provides practical implications for post-discharge management and safety planning. Clinicians should be aware of (1) the increased risk of immediate suicide in the post-discharge period by people with a diagnosis of personality disorder, (2) immediate suicide risk in patients who initiate their own discharge, and (3) the increased risk of death by jumping from a height or in front of the vehicle in the immediate post-discharge period. Our findings support the recent recommendation from NCISH that follow-up should occur within three days of discharge from in-patient care.